Comparative Effectiveness of Dual Antiplatelet Therapy With Aspirin and Clopidogrel Versus Aspirin Monotherapy in Acute, Nonminor Stroke: A Nationwide, Multicenter Registry-Based Study. Issue 11 (November 2019) - Kim, Joon-Tae; Park, Man-Seok; Choi, Kang-Ho; Cho, Ki-Hyun; Kim, Beom Joon; Park, Jong-Moo; Kang, Kyusik; Lee, Soo Joo; Kim, Jae Guk; Cha, Jae-Kwan; Kim, Dae-Hyun; Park, Tai Hwan; et al.
Abstract : Background and Purpose—: This study aimed to compare the effectiveness of dual antiplatelet therapy with clopidogrel plus aspirin (DAPT) with that of aspirin monotherapy (AM) in patients with acute, nonminor, and noncardioembolic stroke. Methods—: Using a prospective, nationwide, multicenter stroke registry database, acute (within 24 hours of onset), nonminor (baseline National Institutes of Health Stroke Scale score, 4–15), and noncardioembolic stroke patients were identified. Propensity scores using inverse probability of treatment weighting were used to adjust baseline imbalances between the DAPT and AM groups. A primary outcome measure was a composite of all types of stroke (ischemic and hemorrhagic), myocardial infarction, and all-cause mortality within 3 months of stroke onset. Results—: Among the 4461 patients meeting the eligibility criteria (age, 69±13 years; men, 57.7%), 52.5% (n=2340) received AM, and 47.5% (n=2121) received DAPT. The primary outcome event was not significantly different between the DAPT group and the AM group (20.9% versus 22.6%, P =0.13). The event rates of all types of stroke were also not different between the 2 groups (19.3% versus 20.1%, P =0.35), while all-cause mortality was significantly lower in the DAPT group than in the AM group (3.4% versus 4.9%, P =0.02). In the propensity-weighted Cox proportional hazards models with robust estimation, DAPT did not reduce the risk of the primary outcome event (hazards ratio, 0.91; 95% CI, 0.79–1.04) but did reduce the risk of all-cause mortality (0.69; 0.49–0.97). There was no treatment heterogeneity among the predefined subgroups, although the potential benefits of DAPT were suggested in subpopulations of moderate-to-severe relevant arterial stenosis and relatively severe deficits (National Institutes of Health Stroke Scale score, 12–15). Conclusions—: Compared to AM, clopidogrel plus aspirin did not reduce the risk of the primary outcome event during the first 3 months after a nonminor, noncardioembolic, ischemic stroke. Abstract : Supplemental Digital Content is available in the text.